An evaluation of Wiedeburg's Method of Diminution for the purpose of stylistic composition : Embellishing Descending-Fifths Sequences in the Style of Bach's Two-part Inventions. - Grönlund, Aapo (My University, 2019)
The objective of this project is to evaluate Michael Wiedeburg's (1720-1800) method of diminution to facilitate the embellishment of descending-fifths sequences in the style of the fifteen Inventions by Johann Sebastian Bach (BWV 772-801). Diminutions constructed with the method by Wiedeburg are compared to select descending-fifths sequences by Bach. Comparisons of Bach's descending-fifths sequences and diminutions constructed with Wiedeburg's method show what additional steps students of stylistic composition need to take to achieve some competency in writing sequences in the style of Bach. Overall, this project highlights aspects of Bach's technique of embellishing descending-fifths sequences. The results of this project indicate that in addition to applying Wiedeburg's method of diminution, one must also apply the diminution techniques Bach uses such as melodic leaps and chordal arpeggiation. One must also utilize the material of the subject since Bach tends to use this material in his sequences.
Keywords: inventiot; diminuutio; säveltäminen; tyylit; mallit; piano